Mnemonic Device Technique Increase Students Vocabulary Mastery - Bambang Nur Alamsyah Lubis; Diani Syahputri (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
This research was conducted to find out the contribution of Mnemonic Device Technique to increase students vocabulary mastery. Descriptive qualitative was used as research method in this research. The source of data was junior high school students at SMP Swasta Yapim Buiru-Biru. The data of this research were students score in vocabulary mastery. The result of this research was Mnemonic Device Technique has specific contribution to increase students vocabulary mastery. Based on five kinds of Mnemonic Device Technique, they are: 1) Rhyme-Keys, 2) acronym, 3) Peg word system, 4) Loci Method, and 5) Keyword Method, the kind that actually increase students vocabulary mastery was Keyword Method. It happened because students were easy to remember something that near from their daily language or something iconic in their language.